Understanding of Religious Figures on Mudharabah Contracts in Sharia Financing Products in Rembatan Wetan Village - Siti Milha Faujiah (Penerbit Hellow Pustaka, 2023)
Over time, the development of Islamic banks in Indramayu will be very rapid but in the development of this Islamic bank there is a problem Which arise from villages in Indramayu where the people don't really understand about products Which There is sharia banking. Type study This use approach qualitative with method Which used frequency distribution _that is aim For know how much big understanding figure religion to contract mudharabah on product financing sharia in the village Expedition Wetan district Sindang Regency. indramayu, whereas collection data use questionnaire or questionnaire Which shared to whole religious leaders in the village of Rambatan Wetan. Conclusion Which can obtained as following : First, understanding the characters religion towards Sharia Banking understand or know by presentation 50% . Second, with the percentage of 35% of religious figures not understand challenge contract mudharabah.